Software for Simplifying Embedded System Design Based on Event-Driven Method - Maman Abdurohman; Arif Sasongko (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Complexity of embedded system application increases along with the escalation of market demand. Embedded system design process must be enhanced to face design complexity problem. One of challenges in designing embedded system is speed, accuracy, and flexibility. The design process is usually conducted recursively to fulfill requirement of user and optimization. To solve this problem, it needs a system design that is flexible for adaptation. One of solutions is by optimizing all or some of the design steps. This paper proposes a design framework with an automatic framework code generator with of event driven approach. This software is a part of a design flow which is flexible and fast. Tron game and simple calculator are presented as a case study. Test result shows that this framework generator can increase speed of design’s flexibility.